How does sustainability affect consumer choices in the fashion industry? - Pereira, L.; Carvalho, R.; Dias, Á.; Costa, R.; António, N. (Resources, 2021)
The fashion industry being one of the most polluting industries in the world means that it is an industry with an immense potential for change. Consumers are central and are closely intertwined with how companies act. This research reflects consumer perspectives and practices towards the topic of sustainability implemented in the fashion industry. The relevance of sustainability in the fashion industry and the key role of consumers in its implementation are undeniable and confirmed by consumers in a representation of general awareness and concern, despite not always being translated into actual practices. A qualitative research methodology, followed by a set of interviews conducted with consumers, revealed that the great majority are implementing a variety of practices when making their buying choices towards fashion items. Barriers such as lack of education, information, knowledge and transparency were identified, and this aspect was shared by consumers as a reason why they are not motivated to make more conscious decisions. Companies should educate consumers from a general perspective and focus on the group of consumers that are not implementing sustainability in the fashion industry in their buying choices, as they represent the potential for the future.